An evaluation framework for future integrated energy systems: A whole energy systems approach. (July 2021) - Berjawi, A.E.H.; Walker, S.L.; Patsios, C.; Hosseini, S.H.R.
Abstract: The energy system is undergoing a transition driven by the need of achieving the energy trilemma objectives: decarbonisation, acceptability and security. Energy systems integration connecting the power, gas, heat and transport systems, is one possible pathway to drive the transition flexibly and cost-effectively. Nevertheless, more quantified evidence on the performance of future integrated energy systems towards achieving policy objectives is still needed for decision makers to support this route. This paper first identifies the expected changes to the energy system upon integration, including new interactions and interdependencies between its components and actors. The paper then argues the need for a whole energy systems approach for the evaluation of integrated energy systems, represented by six characteristics: multidimensional, multivectoral, systemic, futuristic, systematic, and applicability. Based on the identified characteristics, the paper reviews existing evaluation frameworks for energy systems sustainability, and qualitatively appraises their adequacy for evaluating future integrated energy systems. The review concludes that existing frameworks are not capable of assessing the performance of integrated energy systems, lacking one or more of the characteristics. The paper finally presents a novel holistic evaluation framework based on the System-of-Systems approach for systems analysis coupled with an indicator-based approach for evaluation. The proposed framework demonstrates the six characteristics as it enables evaluation with respect to multiple perspectives and objectives at different system levels. Moreover, this framework captures future changes to the whole energy system architecture and highlights the interdependencies between energy systems. This framework can also be systematically applied to various scenarios in different contexts. Highlights: The need for a whole energy systems approach for evaluating integrated energy systems. Inadequacy of existing evaluation frameworks for energy systems sustainability. A novel indicator-based evaluation framework founded on a system-of-systems approach. Validation of the proposed evaluation framework through expert elicitation.